Potential Application of Peppermint (Mentha piperita L.), German Chamomile (Matricaria chamomilla L.) and Yarrow (Achillea millefolium L.) as Active Fillers in Natural Rubber Biocomposites - Masłowski, Marcin (Int J Mol Sci, 2021)
In this study, peppermint (Mentha piperita L.), German chamomile (Matricaria chamomilla L.) and yarrow (Achillea millefolium L.) were applied as natural fibrous fillers to create biocomposites containing substances of plant origin. The purpose of the work was to investigate the activity and effectiveness of selected plants as a material for the modification of natural rubber composites. This research was the first approach to examine the usefulness of peppermint, German chamomile and yarrow in the field of polymer technology. Dried and ground plant particles were subjected to Fourier transmission infrared spectroscopy (FTIR) and UV–Vis spectroscopy, thermogravimetric analysis (TGA), goniometric measurements (contact angle) and scanning electron microscopy (SEM). The characterization of natural rubber composites filled with bio-additives was performed including rheometric measurements, FTIR, TGA, cross-linking density, mechanical properties and colour change after simulated aging processes. Composites filled with natural fillers showed improved barrier properties and mechanical strength. Moreover, an increase in the cross-linking density of the materials before and after the simulated aging processes, compared to the reference sample, was observed.